Gender differences in willingness to move for interregional job offers - Martin Abraham; Sebastian Bähr; Mark Trappmann (Demographic Research, 2019)
Background: Interregional job offers are an important mechanism of social mobility as they provide both career chances and opportunities to avoid unemployment. We know from the literature that couples have difficulties seizing these opportunities due to the unequal distribution of costs and benefits between partners. Consequently, couples generally show a lower willingness to move for a job offer for one of the partners. However, very little is known about the differences between men and women in assessing the attractiveness of a job-related household move. Objective: Focusing on all cohabitating couples, we address whether there are gender differences in willingness to move for a better job offer and how those differences can be explained. Methods: We employ a large household survey from Germany that includes a factorial survey experiment addressing willingness to move for a hypothetical job offer. Results: We find that (a) within couples, women show a lower willingness to move than men, but single women do not differ from single men; (b) variables resulting from standard theories on mobility contribute to the explanation of willingness to move; and (c) gender differences persist even after controlling for these variables. Conclusions: Women show a lower willingness to move for a job when they are living with a partner in a household, and this cannot be sufficiently explained by standard theories of household and family migration. Only gender norms contribute significantly to the explanation of these differences between sexes. Consequently, women are disadvantaged when considering interregional job offers Contribution: Our findings reveal that interregional job offers contribute to gender inequality by hampering the career options of coupled women. A comparison with early results from the United States reveals that this seems to be a general pattern that cannot be explained by standard household migration theories.